COMPARATIVE ANALYSIS OF WATER-BASED INHIBITORS CONTAINING CDEA AND TEA AGAINST API 5L GRADE B - Prabowo, Imam; Ichsanudin, Muhammad; Fuadi, Muhammad; Mussoddaq, Mochamad; Paundra, Fajar (Universitas Majalengka, 2024)
Corrosion of API 5L Grade B steel is a common challenge in industries where the material is exposed to corrosive environments, such as saline solutions. To combat this issue, corrosion inhibitors are often used to protect the steel. This study explores the effectiveness of two inhibitors—Triethanolamine (TEA) and Cocamide DEA (CDEA)—in reducing corrosion on API 5L Grade B steel. By calculating the corrosion rate and inhibitor efficiency, we evaluated the protective properties of each substance. The results showed that TEA provided better corrosion protection, with a corrosion rate of 0.00045 mpy, compared to CDEA’s rate of 0.0009 mpy. Additionally, TEA demonstrated a higher inhibitor efficiency of 70.97%, while CDEA showed only 41.94%. These findings suggest that TEA is a more effective choice for preventing corrosion in API 5L Grade B steel, offering a viable solution to enhance the material’s durability in harsh environments.